Metastatic pancreatic neuroendocrine tumor with ectopic adrenocorticotropic hormone production - Vaduganathan, Muthiah (Proc (Bayl Univ Med Cent), 2015)
We describe a 71-year-old man who presented with abdominal pain, lower-extremity edema, recent unintentional weight loss, hypertension, hyperglycemia, hypokalemia, and metabolic alkalosis. Serum cortisol levels remained elevated after overnight high-dose dexamethasone suppression. Magnetic resonance imaging revealed a small mass in the head of the pancreas with scattered liver metastases. Both endoscopic ultrasound-guided pancreatic biopsy and liver biopsy revealed a well-differentiated neuroendocrine tumor. These lesions did not show significant uptake on octreotide scan. Medical management and hepatic artery chemoembolization were attempted. Ultimately, the patient underwent bilateral adrenalectomy, but died within 4 months of symptom onset secondary to postoperative complications.